Case report: Misdiagnosis of accessory spleen in the left adrenal region as an adrenal tumour after splenectomy - Zou, Yuhua; Xie, Xiaojuan; Yan, Sheng; Wu, Gengqing; Liu, Quanliang (Frontiers in Surgery, 2022)
Adrenal tumours are common in urology and endocrinology，and the diagnosis of adrenal tumours were mainly depends on imaging diagnosis. Howerver, misdiagnosis can still occur for some adrenal space-occupying lesions without specific manifestations or abnormal biochemical indexes. Here we report a patient who the accessory spleen was misdiagnosed as adrenal tumour before the operation. Although the patient had undergone open splenectomy 20 years ago, but the main cause of misdiagnosis was the lack of understanding of accessory spleen before surgery. The left adrenal region mass was removed. In the histological examination, the splenic corpuscle and splenic medullary structure were seen under the microscope, and an accessory spleen was diagnosed. So when the cases show abnormal adrenal space-occupying lesions in imaging examinations, non-adrenal diseases should be considered. We need to combine different imaging techniques for analysis, and think more about it, avoid misdiagnosis leading to unnecessary surgery.